2010
DOI: 10.2139/ssrn.1588732
|View full text |Cite
|
Sign up to set email alerts
|

One Last Puff? Public Smoking Bans and Smoking Behavior

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 30 publications
6
57
5
Order By: Relevance
“…Adda and Cornaglia (2010) draw on time-use data to suggest that following bans, smokers spent more time at home. They argue that bans may have increased children's exposure to second-hand smoke as a result, though the findings have been disputed by Carpenter, Postolek and Warman (2011) Adda and Cornaglia, 2010;Carpenter, Postolek and Warman, 2011;Anger, Kvasnicka and Siedler, 2011;Jones et al, 2011.…”
Section: Bans On Smoking In Public Placesmentioning
confidence: 99%
“…Adda and Cornaglia (2010) draw on time-use data to suggest that following bans, smokers spent more time at home. They argue that bans may have increased children's exposure to second-hand smoke as a result, though the findings have been disputed by Carpenter, Postolek and Warman (2011) Adda and Cornaglia, 2010;Carpenter, Postolek and Warman, 2011;Anger, Kvasnicka and Siedler, 2011;Jones et al, 2011.…”
Section: Bans On Smoking In Public Placesmentioning
confidence: 99%
“…public and private worker, student, home worker) in state s. The CIAPI, which is calculated separately for men and women using gender-specific data, varies across states, and within states, across economic activities. X i is a vector of individual demographic variables that have been found to be correlated with cigarette consumption in previous studies (Wasserman et al, 1991;Tauras, 2006;Anger et al, 2011). It includes the history of smoking (years that the individual has smoked regularly), age, per capita monthly income, highest school grade completed, and, denoting with * the omitted variables, indicators for: technical school, residence in a locality with Oportunidadesa federal social programme that provides nutrition, education and health servicesindigenous status, urban residence, marital status (single*, married, divorced), economic activity (worker*, student, home worker) and region of residence (Southeast, Northwest*, Northeast, Centre and West).…”
Section: Model Specificationmentioning
confidence: 99%
“…Motivated by recent evidence from Germany where it has been found that smoking bans in hospitality industry venues (e.g. bars) does not affect the average person, but reduces tobacco consumption among those who go out more often to bans and restaurants (Anger et al, 2011), the index captures that tobacco control laws impose greater costs, and should hereby be more effective, if more restrictive policies are placed in venues where most individuals spend most of their time. 1 The index also incorporates the enforcement feature of the law, which has been largely ignored despite that lack of 1 Heterogeneous weights have only been used in the construction of an index of national tobacco control programmes (Joossens & Raw, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Carpenter and Cook (2008) show that tobacco tax increases are associated with significant reductions in smoking participation and frequent smoking by youths. Using rich longitudinal data from the German Socioeconomic Panel Study, Anger, Kvasnicka, and Siedler (2011) investigate the impact of public smoking bans on smoking behavior. They find that individuals who go out more often to bars and restaurants adjust their smoking behavior as a response to a public smoking ban and as a result, they become less likely to smoke and also smoke less.…”
Section: Introductionmentioning
confidence: 99%